Prediction of Deterministic All-Optical Switching of Ferromagnetic Thin Film by Ultrafast Optothermal and Optomagnetic Couplings. Issue 1 (December 2017) - Du, Zhidong; Chen, Chen; Cheng, Feng; Liu, Yongmin; Pan, Liang
Abstract All-optical switching (AOS) of magnetization induced by ultrafast laser pulses is fundamentally interesting and promises unprecedented speed for magnetic data storage that is three orders of magnitudes faster than the current techniques. For ferrimagnetic material, the AOS is attributed to magnetic circular dichroism and angular momentum transfer between sublattices. Recently, ferromagnetic material is demonstrated in AOS under multiple pulses. Since the magnetic field needed to flip the ferromagnetic magnetization within femtosecond timescale is unphysically high, some theories hypothesized that there exists a prolonged magnetic field beyond the pulse duration in the switching process. This is intuitively inconsistent with the phenomenological explanation based on the light-induced magnetic field arising from the inverse Faraday effect (IFE). Here, we numerically study the AOS process and provide new insights into the long-standing paradox of the duration of the induced magnetic field. We show that the prolonged magnetic field duration originates from the ultrafast optothermal and optomagnetic coupling. Moreover, we numerically studied both single- and multiple-pulse AOS under different coupling strength between spins and the thermal bath in the macroscopic Fockker-Planck and Landau-Lifshitz-Bloch model. This numerical model may provide a guide to find suitable ferromagnetic materials for AOS.